Abriendo nuevos surcos: ideología, política y labor social de Lázaro Cárdenas en Michoacán, 1928-1932 - Ginzberg, Eitan (El Colegio de México, A.C., 1999)
The question of whether Lázaro Cárdenas was a shrewd politician or a passionate idealist is still a bone of contention among historians. This article examines the issue in the context of his governorship of the state of Michoacán, a subject that has seldom been a focus of research. Contrary to the  argument that Cárdenas saw Michoacán as a springboard to the presidency of the nation rather than a forum for socioeconomic progress and that he merely harnessed already existing popular forces, this article maintains  that Cárdenas not only implemented significant social projects while mobilizing most sectors of local society, but also gave government a new face. He  established new and efficient mechanisms of political power that permitted him  -as intended- to put his revolutionary social ideology into practice. Although his aproach may have  been perceived as cynical  and manipulative, it in fact merely represented an effort to avoid repeating  the shortcomings of  his predecessors, whose lack of effective political power had torpedoed their revolutionary and well-intended social programs.